A MATHEMATICAL MODEL OF GALVANIC CORROSION UNDER THE CONDITIONS OF A THIN ELECTROLYTE FILM - Jeníček , Vít; Diblíková , Linda (České vysoké učení technické v Praze, 2016)
A mathematical model of galvanic corrosion under the conditions of a thin electrolyte film was used to evaluate atmospheric corrosion. Experimentally determined weight loss values were used to validate the modelled results. The time dependence of the corrosion degradation was included in the model using polarization curves of the corroded materials. The difference between the modelled results and the experimental results was 20%, taking the experimental error into account.
Keywords: atmospheric corrosion, galvanic corrosion, modelling, weight loss